Grundschullehramt zwischen Professionalität und De-Professionalisierung. Herausforderungen der Lehrkräftequalifizierung für eine hochwertige grundlegende Bildung in der Grundschule - Rank, Astrid; Büker, Petra; Miller, Susanne; Martschinke, Sabine (Erziehungswissenschaft : Mitteilungen der Deutschen Gesellschaft für Erziehungswissenschaft, 2023)
The article addresses the current challenges in the qualification of teachers at primary schools, highlighting the tension between professionalism and deprofessionalization. It discusses the alarming academic performance of primary school children and the acute shortage of teachers. The authors emphasize the importance of high-quality professionalization of teachers considering the specific standards in primary teacher education. The university phase of teacher education should play a central role in ensuring comprehensive professionalization. Professionalization can not to be limited to practical experience. Various measures to ensure a scientifically grounded professionalization are propose